KEWAJIBAN MASYARAKAT MELAPORKAN PERISTIWA KEMATIAN ANGGOTA KELUARGANYA DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KECAMATAN SINGKAWANG TENGAH DI KOTA SINGKAWANG - NIM. A1012191101, CINTIYA NUR ANISA (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac There are several impacts that result if you don't take care of the death certificate, namely: for the family / heirs will experience problems in terms of: Managing the Determination of Heirs, Taking Care of Retired Widows/Widowers, Managing Insurance Claims. And Implement Remarriage; and for the government the impact will be fictitious data inflation. The person is dead but the data is still there. This has an effect on the Permanent Voter List Data in general elections, both regional and presidential elections. For example, the name of a deceased person can be used by someone to enter the voter list. Because the death certificate was not taken care of or reported to the civil registration service, the name of the deceased is still there. The community feels that it is enough if they hold a death certificate from the village/kelurahan, even though the death certificate from the village/kelurahan is not yet an official document, only a requirement for processing death certificate. Population Documents are said to be official, which are official documents issued by implementing agencies that have legal force as authentic evidence resulting from population registration and civil registration services. In this case the Executing Agency is the Office of Population and Civil Registration.So the main problem formulation in this study is: